Templated Synthesis of Honeycomb-like Tio2 for Supercapacitor Applications - Maria Sarno; Gennaro Gentile; Eleonora Ponticorvo (Chemical Engineering Transactions, 2021)
A facile and cost-effective procedure to synthesize honeycomb-like porous TiO2, which exhibits specific capacitance of 0.2 F/cm2 at 20 mV/s, was proposed. Scanning Electron Microscopy (SEM), thermogravimetric analysis (TG), UV/Vis, Fourier Transform Infrared Spectroscopy (FTIR), and X-ray diffraction (XRD) were employed for characterization. The electrochemical performances of the electrode were investigated in acidic solution.